2015
DOI: 10.31144/bncc.cs.2542-1972.2015.n38.p121-150
|View full text |Cite
|
Sign up to set email alerts
|

Bisimulation for Fluid Stochastic Petri Nets

Abstract: We propose a novel notion of fluid bisimulation equivalence that allows one to compare and reduce the behavior of labeled fluid stochastic Petri nets (LF-SPNs) while preserving their discrete and continuous properties. The underlying stochastic model for the discrete part of the LFSPNs is a continuous time Markov chain (CTMC). The performance analysis of the continuous part of the LFSPNs is accomplished via the associated stochastic fluid models. For the fluid bisimulation on the discrete markings of two LFSPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…• The implication ↔ f l →≡ f l is valid by Proposition 2 from [75]. Let us see that the implication is strict, i.e.…”
Section: Definition 14 Let N and N ′ Be Lfspns Such Thatmentioning
confidence: 92%
See 3 more Smart Citations
“…• The implication ↔ f l →≡ f l is valid by Proposition 2 from [75]. Let us see that the implication is strict, i.e.…”
Section: Definition 14 Let N and N ′ Be Lfspns Such Thatmentioning
confidence: 92%
“…Previous works and outline of the paper. The previous results on the fluid equivalences can be found in [74,75], where we have proposed a class of LFSPNs, for which we have defined fluid trace and bisimulation equivalences and investigated their interrelations. We have shown that fluid trace equivalence preserves average potential fluid change volume for the transition sequences of every certain length.…”
Section: Logical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first results on this subject can be found in [73], where we have proposed a class of LFSPNs and defined a novel behavioural relation of fluid bisimulation equivalence for them. We have also proven there that the equivalence preserves aggregate fluid density and distribution, as well as discrete and continuous performance measures.…”
Section: Previous Work and Contributions Of The Papermentioning
confidence: 99%